Metro ethernet services for LTE backhaul - Krzanowski, Roman (Artech House mobile communications series, 2013)
The backhaul portion of the network is comprised of intermediate links between the core network and the small sub-networks at the "edge" of the entire hierarchical network. This practical resource serves as a comprehensive guide to designing mobile Ethernet backhauling (MEBH) services in metro areas using carrier Ethernet (CE) architecture